The Effect of Financial Literacy on Financial Management of Msmes in the Pantura Area, Subang Regency - Titin Kartini; John Henry Wijaya (SAFE-Network, 2023)
The empowerment of MSME actors is very important because it is related to its function as a driving force for the economy of a country through micro, small, and medium enterprises. This study aims to describe the level of financial literacy that can influence the movement of micro, small, and medium enterprises in MSME actors in the Pantura Region of Subang Regency with experience, economic status and culture and social environment, self-efficacy, and attitude. The method used in this research is descriptive quantitative. The object of this research is MSME actors in the Pantura area of Subang Regency with a total sample of 100 respondents using a simple random sampling technique and obtaining data through a questionnaire. The results of the study show that experience, economic status and social culture and environment, self-efficacy, and attitude affect financial literacy.